Atomistic Insights into the Effects of Residual Stress during Nanoindentation - Kun Sun; Junqin Shi; Lifeng Ma (Crystals, 2017)
The influence of in-plane residual stress on Hertzian nanoindentation for single-crystal copper thin film is investigated using molecular dynamics simulations (MD). It is found that: (i) the yield strength of incipient plasticity increases with compressive residual stress, but decreases with tensile residual stress; (ii) the hardness decreases with tensile residual stress, and increases with compressive residual stress, but abruptly drops down at a higher compressive residual stress level, because of the deterioration of the surface; (iii) the indentation modulus reduces linearly with decreasing compressive residual stress (and with increasing tensile residual stress). It can be concluded from the MD simulations that the residual stress not only strongly influences the dislocation evolution of the plastic deformation process, but also significantly affects the size of the plastic zone.